Analisis Kerentanan Gedung Menara FMIPA UNM Berdasarkan Pengukuran Mikrotremor Dengan Metode FSR (Floor Spectra Ratio) - Yuliana, Riska; Sulistiawaty, Sulistiawaty; Susanto, Agus (Progressive Physics Journal, 2024)
Research has been conducted on vulnerability analysis of Gedung Menara FMIPA UNM based on microtremor measurements using the FSR (Floor Spectra Ratio) method. The purpose of this study was to analyze the data from microtremor measurements using the FSR (Floor Spectra Ratio) method so that natural frequency, amplification, and vulnerability values of Gedung Menara FMIPA UNM were obtained. The measurements were made using a set of portable measuring instruments TDL 303 S Seismograph to record vibrations. Measurements were made at 37 points in the building and 3 points in the area around the building. Recording data is processed using Geopsy with FSR method. The results of the study obtained the natural frequency of the Gedung Menara FMIPA UNM for each component was 1.3047 Hz to 2.3823 Hz in the NS component and 1.0556 Hz to 2.4355 Hz in the EW component. The amplification of the Gedung Menara FMIPA UNM for each component is 306.8593 to 2850.7233 in NS components and 360.975 to 4783.54 in EW components. The vulnerability value of the Gedung Menara FMIPA UNM for each component is to in NS component and to in EW component. Gedung Menara FMIPA UNM has complied with SNI 1726-2002. The 12nd floor is the part with the highest building vulnerability.